INTEGRATING PHYSICAL ACTIVITY INTO THE RECOVERY PATHWAY AFTER BREAST CANCER – A NARRATIVE REVIEW - Maciej Borowski; Natalia Śliwa; Eliza Kawalska; Kacper Zielonka; Bartosz Dądela; Sara Langner; Szymon Janczura; Szymon Gnitecki; Marcin Markowski; Joanna Jasińska (International Journal of Innovative Technologies in Social Science, 2025)
Breast cancer remains the most frequently diagnosed malignancy among women worldwide. Although surgical approaches, being the first-line treatment in most cases of breast cancer, such as mastectomy and breast-conserving therapy (BCT), often combined with sentinel lymph node biopsy (SLNB) or axillary lymph node dissection (ALND), are critical for disease management, they are often accompanied by a range of physical, psychological, and functional challenges that persist well beyond the perioperative period. Throughout recent years, structured physical activity has gained recognition as a non-pharmacological intervention aimed in reducing adverse effects adverse effects of surgical intervention in breast cancer. This narrative review summarizes findings from studies published between 2002 and 2025 about the role of physical activity in breast cancer treatment, focusing specifically on the postoperative period. The findings show a range of physical activities and how some of them can support recovery after surgery. They can improve lymphatic and musculoskeletal function. They also help reduce cancer-related fatigue, pain, and emotional distress. Of note, the extent of benefit varies depending on the type of surgical procedure. For example mastectomy patients generally requiring more extensive rehabilitation than those after regular BCT. Despite all these differences, individualized exercise programs have been associated with significant improvements across diverse clinical contexts. Given its proven efficacy and safety, physical activity should be regarded as a intrinsic element of integrative breast cancer care, included in both perioperative protocols and long-term survivorship plans. Future studies should focus on developing precision-based exercise models. They should also explore the biological mechanisms that connect specific movements to recovery and resilience.